Molecular Characterization of Antibiotic Resistance Genes in Hospital-Acquired Urinary Tract Infections - Khan, Sumia; Malik, Infal; Khan, Laiba; Jan, Fauzia; Gangi, Andrea; Siddiqa, Ayesha; Tabassum, Taiba; Khan, Muhammad Noman; Bukhari, Nain Taara (Indus Journal of Bioscience Research, 2025)
Introduction: Hospital-acquired urinary tract infections (HAUTIs) represent a major challenge in healthcare due to increasing multidrug resistance (MDR) among causative pathogens. Objective: This study aimed to molecularly characterize antibiotic resistance genes in bacterial isolates from HAUTI patients and assess their antimicrobial susceptibility profiles. Methodology: A total of 150 urine samples were collected from hospitalized patients diagnosed with HAUTIs. Bacterial isolates were identified using standard microbiological methods, and antibiotic susceptibility testing was performed following Clinical and Laboratory Standards Institute (CLSI) guidelines. Phenotypic screening for extended-spectrum beta-lactamase (ESBL) and carbapenemase production was conducted, followed by polymerase chain reaction (PCR) assays targeting key resistance genes including bla_CTX-M, bla_TEM, bla_SHV, bla_NDM, bla_OXA-48, and bla_KPC. Results: Out of 114 isolates recovered, Escherichia coli (40.4%) and Klebsiella pneumoniae (24.6%) were predominant. High resistance rates were observed against third-generation cephalosporins, fluoroquinolones, and carbapenems, with 68.4% of isolates classified as MDR. ESBL production was confirmed phenotypically in 57.0% of isolates, predominantly in E. coli and K. pneumoniae. Carbapenemase activity was detected in 25.4% of isolates, especially in K. pneumoniae and Acinetobacter baumannii. PCR analysis revealed bla_CTX-M as the most prevalent gene (66.7%), followed by bla_TEM (48.7%) and bla_NDM (26.9%). Conclusion: Co-occurrence of multiple resistance genes was common, highlighting the complexity of resistance mechanisms. The study underscores the critical need for continuous molecular surveillance and stringent antimicrobial stewardship to effectively manage HAUTIs and prevent the spread of resistant pathogens in healthcare settings.